The Role of High Resolution Sonography in the Evaluation of Anterior Abdominal Wall Lesions - C. Arpita; C Ananda Reddy (Asian Journal of Medical Research, 2019)
Background: Clinical presentation of anterior abdominal wall pathologies are non-specific. Based on physical examination alone, it is often difficult to diagnose the specific anterior abdominal wall pathologies. The aims of the study were, to evaluate accuracy of the high-resolution sonography in the diagnosis of anterior abdominal wall pathologies.Subjects and Methods:All patients referred to the Department of Radiodiagnosis with the clinical manifestations of various anterior abdominal lesion in a period of 2 years, were subjected for the study. 50 cases were taken up for the study. All patients included in the study underwent anterior abdominal wall ultrasonography using 7.0-12.0 MHZ high frequency linear array transducer coupled with color doppler equipment. This was followed by pelvic scan using 3.5-5.0 MHZ transducer whenever required. Findings during surgery and histopathology reports were noted and compared with the sonographic features.Results:Our study showed high prevalence of anterior abdominal lesions in patients between the age group of 20-40 years which constituted 60% of all cases. Most common presentation was seen in females (66%). Incisional hernia was the predominant anterior abdominal wall lesion constituting 44%, followed by ventral hernias14% lipomas and hematomas both were seen in 8% of cases. Least common was anterior abdominal wall sarcoma seen in 2% cases. Higher resolution sonography is an accurate method for assessment of anterior abdominal wall lesions. Sensitivity of 100%, specificity of 75%, PPV of 97.4%, NPV of 100%. In total diagnostic accuracy of high-resolution sonography was 97.6% in our study.Conclusion: High resolution sonography is an accurate diagnostic imaging modality in anterior abdominal wall lesions. It is also highly sensitive in differentiating hernias from cystic or solid abdominal wall lesions.